Conceptions et définitions de la sexualité: les différentes approches - Courtois, Robert (Ann. Méd., 1998)
The author proposes a reflection on the definition of the human sexuality in social sciences. The profusion of ideas of the sexuality refer to different disciplines. It does not seem to avoid a certain poverty in the definition of the sexuality. It is possible that trivial character defers to a more rigorous definition. Polymorphous aspect of sexuality obliges to have recourse to ideas that have several dimensions and that are therefore more difficult for categorize. The sexuality is both an individual datum, perhaps personal or intimate and at the same time interpersonal and collective. It is an important factor of socialization. Sexuality and social, sexuality and culture are always indissociable. This question of the definition of sexuality is analyzed to the breadth a great number of different approaches : phylogenetic, psychological, anthropological, medical biological points of view, psychoanalytical and psychopathology concepts.